Pipette-tip μSPE coupled with HPLC-MS/MS for trace determination of fluoroquinolones in human urine - Francesca Merlo; Petra Bianchini; Federica Maraschi; Andrea Speltini; Antonella Profumo (Talanta Open, 2023)
A microextraction procedure was developed for the determination of fluoroquinolone (FQ) drugs, namely Ciprofloxacin, Levofloxacin, Lomefloxacin, Moxifloxacin, Norfloxacin and Sparfloxacin, in human urine. The new natural waste-derived material consisting of silica-supported carbon nanoparticle aggregates from rice husk ash (nC-RHA@SiO2) was used as sorbent for setting up a straightforward pipette-tip micro-solid-phase extraction (PT-µSPE) prior to HPLC-MS/MS quantification. The analytes were adsorbed on the solid phase (25 mg) through multi-type interactions and, after a washing step (0.1 % v/v formic acid, 5 % v/v ethanol), eluted in alkaline aqueous solution (15 % v/v acetonitrile), thus achieving simultaneous extraction and clean-up. The PT-µSPE coupled with MS2 detection provided satisfactory recovery (67–118 %, n = 3) in 1:1 v/v diluted urine samples (formate buffer, pH 3), good inter-day precision (RSD < 12 %), good matrix-matched linearity in the concentration range 3–80 μg L −1 (R2 > 0.9956), and limited matrix effect. The experimental method quantification limit was 5 µg L −1, suitable for trace determination of such drugs in urine. Compared to the actual microextraction procedures, the PT-µSPE described here is attractive in terms of extraction efficiency, sample throughput, energy consumption, limited use of organic solvents and ease of operation, as evidenced by a greenness evaluation through the AGREEprep software. The final method was applied to FQs determination in blind urine samples.